Outbreak of foodborne gastroenteritis in a senior high school in South-eastern Ghana: a retrospective cohort study - Donne K. Ameme; Holy Alomatu; Albert Antobre-Boateng; Adam Zakaria; Lilian Addai; Klutse Fianko; Bai Janneh; Edwin A. Afari; Kofi M. Nyarko; Samuel O. Sackey; Fred Wurapa (BMC, 2016)
Abstract Background On 4th February 2015, a group of Senior High School students from Fanteakwa district presented to the emergency unit of the district hospital with complaints of abdominal pain, vomiting and diarrhoea. All the students had eaten from a specific food vendor and had neither eaten any other common meal that day nor the previous day. A foodborne disease outbreak was suspected. We investigated to verify the outbreak, determine its magnitude, identify the source and implement control measures. Methods A retrospective cohort study was conducted. We reviewed medical records and interviewed patrons of the food vendor. We collected data on age, sex, signs and symptoms, date of illness onset, date of admission, date of discharge, treatments given and outcome. A case of foodborne disease was any person in the school with abdominal pain, vomiting and or diarrhoea from 4th to 11th February 2015 and had eaten from the food vendor. We conducted active case search to identify more cases. We conducted environmental assessment and collected clinical and food samples for laboratory testing. Descriptive and inferential statistical analyses were performed using Stata 12.0. Results A total of 68 cases were recorded giving overall attack rate of 35.79 % (68/190) with no death. Of these, 51.47 % (35/68) were males. Mean age of case-patients was 17.8 (standard deviation +/-1.62). The index case, a 17-year-old female student ate from the food vendor on 4th February at 9:00 am and fell ill at 3:40 pm later that day. Compared to those who ate other food items, students who drank water from container at the canteen were more likely to develop foodborne disease at statistically significant levels [RR = 2.6, 95 % CI = (2.11-3.15)]. Clostridium perfringens (C. perfringens) and Salmonella species (Salmonella spp) were isolated from water and stew respectively. Clinical features of case-patients were compatible with both organisms. Conclusion A foodborne gastroenteritis outbreak occurred in a Senior High School in Fanteakwa District from 4th to 7th February 2015. The most probable aetiologic agent was C. perfringens with contaminated water at canteen as the vehicle of transmission. Concurrent Salmonella spp infection could not be ruled out. Rapid outbreak response helped in controlling the outbreak.